2012
DOI: 10.1177/0363546512462123
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Single-Row Modified Mason-Allen Repair Versus Double-Row Suture Bridge Reconstruction for Supraspinatus Tendon Tears

Abstract: The clinical results after modified Mason-Allen single-row versus double-mattress suture bridge technique did not demonstrate significant differences in a matched patient cohort. Concerning the failure mode, single- and double-row techniques seem to demonstrate different re-defect patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 63 publications
0
80
0
11
Order By: Relevance
“…When sutures cut through tendon, they tend to slip along the longitudinal orientation of the collagen fibers, analogous to passing a comb through a bundle of hair. Especially in arthroscopic repair, mechanically robust suture configurations (eg, modified MasonAllen,) are technically demanding and generally too time consuming to be clinically viable [31] and even shows no superiority in clinical results [9,20]. More simple (eg, double rows of single-loop suture) reconstruction techniques have been shown to provide adequate biomechanical strength, but also raise biological concern attributable to over-tensioning of the repair and incidence of intratendinous retearing [2].…”
Section: Discussionmentioning
confidence: 99%
“…When sutures cut through tendon, they tend to slip along the longitudinal orientation of the collagen fibers, analogous to passing a comb through a bundle of hair. Especially in arthroscopic repair, mechanically robust suture configurations (eg, modified MasonAllen,) are technically demanding and generally too time consuming to be clinically viable [31] and even shows no superiority in clinical results [9,20]. More simple (eg, double rows of single-loop suture) reconstruction techniques have been shown to provide adequate biomechanical strength, but also raise biological concern attributable to over-tensioning of the repair and incidence of intratendinous retearing [2].…”
Section: Discussionmentioning
confidence: 99%
“…18) Recent suture bridge technique had generally reduced the retear rate compared with more conventional technique. 4,6,8,9,19,20) Many authors reported the retear rate from 8%…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] A recent systematic review also underscored that the knot-tying of the medial row is superior to non-tying methods in the biomechanical aspect. 7) However, there is an increasing concern that strangulation of the medial tendinous portion can be elicited by multiple medial knot-tying, resulting in subsequent deterioration of tendon viability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations